Pengaruh Label Halal Terhadap Keputusan Pembelian Daging Ayam - Radlyah Hasan Jan; Fadlun Nabila Bachdar; Faradila Hasan (ARBITRASE: Journal of Economics and Accounting, 2022)
This thesis examines the effect of halal label on purchasing decision of chicken meat at Jumbo Supermarket in Manado City. The main problem in this research is whether the halal label has an effect on purchasing decision of chicken meat at Jumbo Supermarket in Manado City or not. The purpose of this research was to find out the effect of halal label on purchasing decision of chicken meat at Jumbo Supermarket in Manado City. The type of research in this study was quantitative. The population and sample were 96 people at Jumbo Supermarket in Manado City by using the Lameshow formula. The data used in this study were primary data and secondary data. The data analysis technique used in this study was normality test, linearity test, hypotesis test which used the regression test. The results obtained that the halal label had an effect on purchasing decision as evidenced by the results of the analiysis using the coefficient of determination (R2) technique. It showed that the coefficient between the variables of X (Halal Label) and Y (Purchasing Decision) were 0,471 or 47,1%. In addition, based on the siqnificance value of the coefficients, it was obtained that a siqnificance value of 0,000 < 0,05. It means that H0 is rejected and Ha is accepted. The siqnificant and the effect of halal label on purchasing decision are 46,1% while the remaining 52,9% is influenced by other factors which are not examined in this research.